If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -13 = 5 Reorder the terms: -13 + 3n = 5 Solving -13 + 3n = 5 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 3n = 5 + 13 Combine like terms: -13 + 13 = 0 0 + 3n = 5 + 13 3n = 5 + 13 Combine like terms: 5 + 13 = 18 3n = 18 Divide each side by '3'. n = 6 Simplifying n = 6
| 9d+3d-4=5d | | 2x-5(3x-1)=-8 | | -(y-3)=2y+3-3y | | .6x+8=41 | | 9+b=24 | | 9-2*b=1 | | (x-3)(x^2-6x)=7 | | 5x=-3x+35 | | 5(Y+4)=6u | | u-2+-11=-15 | | -1200m+45=-1800m+60 | | 3x(4)=2x(6) | | -10+3*d=-16 | | y=20t-5t^2 | | 4x-10=8-5x | | [9+3(5-7)]=-3 | | t*2+-6=-3 | | a(b-c)=b | | 2x-18=6x+2 | | T=5x^2 | | -6r+2(r+2)-5=-29 | | 8+3*p=17 | | 5(x-3)=3x+2+2x | | 8(x-20)=3(x+3) | | 9x=6+6 | | T=sqrt(25) | | f(x)=3x[squared]-3x | | 36t^2-96t+48=0 | | 2(t+3)=5(t-1)-7(t-3) | | 177+0= | | 4s+8s+3=0 | | 11x-12=4x-1 |